Education and Training on Making Kelakai Syrup (Stenochlaena Palustris (Burn. F) Bedd.) as a Medicinal Plant: Edukasi dan Pelatihan Pembuatan Sirup Kelakai (Stenochlaena Palustris (Burn. F) Bedd.) Sebagai Tanaman Berkhasiat Obat - Hafiz Ramadhan; M. Andi Chandra; Dyera Forestryana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Herbal drinks are a cultural heritage given by our parents that are useful in increasing our immunity. Until now, there are still many people who choose to consume herbal drinks because they are sourced from natural plant materials so that they do not cause side effects and harmful reactions to the body. This Community Service is located in North Landasan Ulin Village, Liang Anggang District. Banjarbaru City where the target is women. Providing education and training on making mandarin syrup (Stenochlaena Palustris (Burn. F) Bedd.) which has the potential to increase immunity. The results of this community service activity showed that the knowledge of making mantle leaf syrup has increased in the percentage of knowledge from the pretest and posttest scores by 70% and residents are able to make a syrup product that has the potential to be efficacious as traditional medicine during the covid-19 pandemic.